‘Amaliyah al-Ittiṣāl al-Lugawi fī Qaṣaṣ Sūrah al-Kahfi - Aly Aulia (IAIN Salatiga, 2022)
The Qur'an, a holy book revealed by Allah SWT, contains the rules and stories of the previous people to strengthen the truth of Islam. In these stories, there is communication between important figures of the previous people, which contains beautiful literary values so that humans easily understand them. One of them is surah al-Kahf which summarizes four important stories: Ashabul Kahf, Owner of two gardens, Musa and Khidlir, and Dzulqarnain, which contain many unusual functional sentences which show the miraculous factor of the Qur'an from a linguistic perspective. This study aimed to reveal communication (speech) acts and the influence of context on word choice and coherence on the principles of speech contained in the story in finding a model of polite speech acts and felt by the interlocutor more lightly. This research was a pragmatic study that used descriptive qualitative methods through a literature review. In order to describe this speech behavior, this study used the speech acts theory developed by Searle. The analysis showed that various speech acts were performed, namely assertive, directive, commissive, expressive, and declarative, with a specific form of expression or language.